Home » Blog » Find the solution of 2y′′ + 3y′ = 0 for given initial values

Find the solution of 2y′′ + 3y′ = 0 for given initial values

Find the particular solution of the differential equation

    \[ 2y'' + 3y' = 0 \]

satisfying the initial condition y = 1 and y' = 1 when x = 0.


First, we rewrite the equation as

    \[ 2y'' + 3y' = 0 \quad \implies \quad y'' + \frac{3}{2} y' = 0. \]

Therefore, this is a second-order linear differential equation of the form

    \[ y'' + ay' + by = 0 \qquad \text{with} \qquad a= \frac{3}{2}, \ \ b = 0. \]

These values of a and b give us d = a^2 - 4b = \frac{9}{4}. So, d> 0 and k = \frac{1}{2} \sqrt{d} = \frac{3}{4}. By Theorem 8.7 (pages 326-327 of Apostol) we then have

    \begin{align*}  &&y &= e^{-\frac{ax}{2}} (c_1 u_1 + c_2 u_2) & u_1 = e^{kx}, \quad u_2 = e^{-kx} \\ \implies && y&= e^{-\frac{3x}{4}} \left( c_1 e^{\frac{3x}{4}} + c_2 e^{-\frac{3x}{4}} \right) \\ \implies && y&= c_1 + c_2e^{-\frac{3x}{2}}. \end{align*}

Therefore,

    \[ y' = -\frac{3}{2} c_2 e^{-\frac{3x}{2}}. \]

We then use the initial conditions y(0) = 1 and y'(0) = 1 to solve for c_1 and c_2,

    \begin{align*} 1 = y'(0) &= -\frac{3}{2} c_2 & \implies && c_2 = -\frac{2}{3} \\ 1 = y(0) &= c_1 + c_2 & \implies && c_1 = \frac{5}{3}. \end{align*}

Therefore,

    \[ y = \frac{5}{3} - \frac{2}{3} e^{-\frac{3x}{2}}. \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):